TELEGRAM AS A MEDIUM OF ACADEMIC INTERACTION (Study of Academic Use and Services for Students of the Faculty of Islamic Religion, Nurul Jadid University) - ronal dhino (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
Telegram is so popular on the campus of Nurul Jadid University, especially at the faculty of Islamic religion since 2018 students as active users. The development of the function of using Telegram, there are several factors, one of which is due to busyness and to make it easier for lecturers who require students and lecturers to conduct learning and notification of information through online media and especially on this campus that utilizes Telegram media. The purpose of this study is to describe Telegram which has relevant features in online information notifications from academic faculty, as well as to obtain illustrations of the process of student information communication to lecturers who use telegraph communication media. A qualitative descriptive approach was used in this study. Telegram is used as a correlation of students to lecturers is a communication process where it uses the internet and digital media when communicating as infrastructure tools from sopport media during the course ofacademic information communication, the use of telegram as the main benefit of communication to ease students in receiving academic information. Researchers get illustrations of all experience processes in using telegrams as academic information communication between education staff and students. Interpersonal communication via telegram can be a substitute medium when students and lecturers do not allow face-to-face interaction in progress. Information is sent via telegram to students. This motivates students, in improving academic activities such as paper consultation.